Forecasting the trajectory of electric vehicle sales and the consequences for worldwide CO2 emissions. (10th July 2020) - Rietmann, Nele; Hügler, Beatrice; Lieven, Theo
Abstract: Over the past decade, global sales of electric vehicles (EVs) have experienced significant growth. However, predictions of future sales developments, which are needed for the planning of EV production as well as supporting policies and a sufficient energy supply, are still sparse. In this study, a long-term forecast of the EV inventory in 26 countries across five continents is provided by means of a logistic growth model. Using actual sales data from 2010 to 2018, predictions were made for these countries until 2035. Findings indicate that, overall, 30% of the worldwide passenger vehicle fleet will be EVs in 2032. However, results also display vast differences between countries, which can particularly be attributed to divergences in governmental support. EV growth predictions were additionally analyzed in terms of sustainability impacts. The analysis showed that reductions in CO2 emissions can be achieved with the predicted EV growth, given that countries invest heavily in renewable energy sources. Given the current energy mixes though, worldwide CO2 emissions will continue to rise until 2035 despite a nearly 50% share of EVs. The paper further discusses the amount of energy that will be required to meet the growing demand and highlights that the production of EV batteries will be the key bottleneck in the development of EVs. Finally, important implications for policymakers, marketers and future research are derived. Graphical abstract: Image 1 Highlights: In 2032, 30% of all passenger cars worldwide are predicted to be EVs. Despite an almost 50% share of EVs in 2035, CO2 emissions will continue to rise. EV growth reduces CO2 emissions if countries adapt low emission electricity mixes.